2024
DOI: 10.1126/sciadv.adg7380
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CGRP receptor–mediated signaling promotes tendon-bone healing

Xibang Zhao,
Guanfu Wu,
Jing Zhang
et al.

Abstract: Calcitonin gene-related peptide (CGRP), an osteopromotive neurotransmitter with a short half-life, shows increase while calcitonin receptor-like (CALCRL) level is decreased at the early stage in bone fractures. Therefore, the activation of CALCRL-mediated signaling may be more critical to promote the tendon-bone healing. We found CGRP enhanced osteogenic differentiation of BMSCs through PKA/CREB/JUNB pathway, contributing to improved sonic hedgehog (SHH) expression, which was verified at the tendon-bone interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
2
0
0
Order By: Relevance
“…Their results showed striking reductions/increases in mineralization markers and bone volume following the silencing/overexpression of the CGRP receptors, similar to the findings of the orthodontic implant study [99]. This demonstrated that increasing the expression of CGRP receptors at the earlier time points, when CGRP levels peak, dramatically improves bone healing [101]. We hypothesize that the prolonged peak of CGRP in our Tgfbr2 cko mice led to the CGRP being present when the receptor expression levels were higher, which allowed for additional mineralization signals in the absence of Tgfbr2.…”
Section: Discussionsupporting
confidence: 68%
“…Their results showed striking reductions/increases in mineralization markers and bone volume following the silencing/overexpression of the CGRP receptors, similar to the findings of the orthodontic implant study [99]. This demonstrated that increasing the expression of CGRP receptors at the earlier time points, when CGRP levels peak, dramatically improves bone healing [101]. We hypothesize that the prolonged peak of CGRP in our Tgfbr2 cko mice led to the CGRP being present when the receptor expression levels were higher, which allowed for additional mineralization signals in the absence of Tgfbr2.…”
Section: Discussionsupporting
confidence: 68%
“…Their results showed striking reductions/increases in mineralization markers and bone volume following the silencing/overexpression of the CGRP receptors, similar to the findings of the orthodontic implant study [31]. This demonstrated that increasing CGRP receptors at the earlier timepoints when CGRP levels peak dramatically improves bone healing [33]. We hypothesize that the prolonged peak of CGRP in our Tgfbr2 cko mice was present when the receptor expression levels would be higher, which allowed for additional mineralization signals in the absence of Tgfbr2.…”
Section: Discussionsupporting
confidence: 66%